2011
DOI: 10.4161/psb.6.1.13545
|View full text |Cite
|
Sign up to set email alerts
|

Development of Casparian strip in rice cultivars

Abstract: Plant roots are in direct contact with the soil environment and thus particularly affected by unfavorable conditions. To withstand the surrounding environment, roots have developed anatomical and physiological adaptations. The development of Casparian strips (CSs) in the root endo-and exodermis is one such strategy. [1][2][3] In roots of most species, the sequence of development of the endo-and exodermis is roughly the same and involves two consecutive developmental stages: (1) formation of CSs in radial and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…The specificity of the Nile red dye to different ontogenetic stages of endodermal development remains relatively unexplored. On the other hand, techniques of fluorescent staining with FY described by Brundrett et al (1988 , 1991 ) have been followed by many researchers in studies of exodermis and endodermis of roots, or suberized cell layers ( Lux et al 2005 ; Cai et al 2011 ; Martinka et al 2012 ; Zelko et al 2012 ; Krishnamurthy et al 2014 ; Soukup and Tylová 2014 ; Rossi et al 2017 ). Different stages of endodermal and exodermal development can be distinguished by staining with BH and FY.…”
Section: Resultsmentioning
confidence: 99%
“…The specificity of the Nile red dye to different ontogenetic stages of endodermal development remains relatively unexplored. On the other hand, techniques of fluorescent staining with FY described by Brundrett et al (1988 , 1991 ) have been followed by many researchers in studies of exodermis and endodermis of roots, or suberized cell layers ( Lux et al 2005 ; Cai et al 2011 ; Martinka et al 2012 ; Zelko et al 2012 ; Krishnamurthy et al 2014 ; Soukup and Tylová 2014 ; Rossi et al 2017 ). Different stages of endodermal and exodermal development can be distinguished by staining with BH and FY.…”
Section: Resultsmentioning
confidence: 99%
“…The exodermis and the endodermis are the outer- and innermost cortical layers of a root, and serve as filtration sites for the passive movement of ions between the soil solution and the stele (Ma and Peterson, 2003). These are the root tissue layers where rice deposits Casparian strips, which act as apoplastic diffusional barriers (Cai et al, 2011). Interestingly, work in Arabidopsis showed that Casparian strips are entirely made of a lignin polymer without suberin, contrary to what was previously accepted (Naseer et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The difference FT-MIR spectra revealed that the content of suberin as well as other cell wall component was higher in the resistant rice cultivar than in the two susceptible cultivars (Cai et al, 2011). …”
Section: The Use Of Ft-mir Spectroscopy To Study Changes In Cell Wallmentioning
confidence: 96%